Política de Atenção à Saúde e Segurança do Trabalho do Servidor Público Federal: avaliação de sua implantação na Universidade Federal do Ceará (UFC) - Taissuke, Andreia Serafim de Negreiros (2016)
There wasn’t any specific regulation for issues related to the federal public servant health for quite a long time, Only since 2003, various laws have been published, culminating with the National Policy on Health Care and Safety at work for the Federal Civil Servants. There was the (PASS) in 2008 and the implementation of the Integrated Subsystem of Health Attention of the Federal Public Server (SIASS) in 2009. At the Federal University of Ceará (UFC) that policy was implemented from 2011 when it was signed, with over fourteen other federal agencies, the Technical Cooperation Agreement (TCA) and created the unit SIASS / UFC, which aimed to offer expertise and surveillance services as well as health promotion to employees of that institution. This study aims to analyze the PASS implementation process within the UFC through the assistance axes, expertise, promotion and health surveillance within the period from 2011 to 2014. The research has basic and strategic nature, being developed as a case study of quantitative and qualitative character. The research field covers the Coordination of Life Quality at Work (COQVT) and the Coordination of Expertise and Assistance to the Server and the Student (CPASE), who are responsible for implementing the PASS. The universe research of the study was a kind of intentional sample of 77 subjects, including managers and staff. The bibliographic and documentary review was adopted as methodological procedure. To collect data, we used questionnaire with the Likert scale for servers and semi-structured interviews for managers. For interpreting the data, we used content and discourse analysis. The study allowed us to conclude that the PASS at the UFC should be strengthened as a public policy and that there is need to establish clear rules for creating SIASS units. The results demonstrated that the SIASS UFC unit has developed several projects, however, the number of servants benefited with it is still small considering the staffing level of the institution, and the actions are concentrated in the capital. Finally, there must be investment in training of the multidisciplinary team, besides improving the integration to describe the planning of actions and services in occupational health. From this perspective, it is expected that this study can contribute to the discussion of the PASS at the UFC and support management decisions.